The Impact of Foreign Direct Investment Spillover, Technology and Firm Size on the Productivity of Domestic Firm in Food Industry - Yuliani, Fitria; Siregar, Hermanto; Widyastutik, Widyastutik; Rifin, Amzul (International Journal of Economics and Financial Issues, 2019)
Foreign direct investment (FDI) is necessary for Indonesia since the rate of saving is still low compared to the higher demand for investment in Indonesia. FDI contributes not only to the higher rate of investment but also to the spillover of other industrial sectors through technology transfer. The FDI spillover could be in the form of horizontal or vertical spillover with upstream and downstream linkages. The spillover of FDI can give a positive or negative impact on the productivity of sectors or other industries. The objective of this study is to analyze the impact of FDI spillover on the productivity of the domestic food industry. The food industry had the highest value of FDI during 1990-2014, but it had a low value of total factor productivity. The research results show that the FDI spillover gives positive impact to the productivity of domestic food industry which has the highest foreign investment with upstream and downstream linkages. The horizontal and vertical spillover of FDI on upstream linkages gives positive impact to big domestic companies with higher levels of technologies. Meanwhile, the vertical spillover of FDI on downstream linkages gives positive impact to local companies with lower levels of technologies. Keywords: Domestic Food Industry, Foreign Direct Investment, Horizontal Spillover, Vertical Spillover, Productivity JEL Classifications: F21; E22; C23; O33 DOI: https://doi.org/10.32479/ijefi.7905